1984
DOI: 10.1111/j.1439-0485.1984.tb00311.x
|View full text |Cite
|
Sign up to set email alerts
|

Subtidal Benthic Macroinfauna in an Estuary of South Chile: Distribution Pattern in Relation to Sediment Types

Abstract: Abstract. A quantitative survey (18 stations) of the subtidal soft bottom macroinfauna in an estuary of the south Chilean coast was conducted during January, 1980. The map of sedimentological facies elaborated for the Queule River Estuary shows sandy bottoms in the outlet and upper part of the area studied, while the middle part is occupied by muddy sand. The ordination of stations by Principal Component Analysis is fundamentally defined by mud and gravel percentage and is, in general, concordant with the dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
4

Year Published

1985
1985
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 17 publications
0
7
0
4
Order By: Relevance
“…Nuevas investigaciones deberán corroborar si el actual patrón de distribución espacial de S. uncina-tus o de la macrofauna intermareal de bahía Lomas puede obedecer a una disminución de la salinidad provocada por el río Side (Sanders et al 1965;Dávila et al 2002), o a cambios en la composición de los sedimentos, o cómo este aporte de agua dulce y la disminución de la salinidad puede fragmentar la población de este poliqueto, de un modo similar a como ha sido sugerido en Punta Arenas para una población del poliqueto Prionospio orensanzi afecta a descargas del río Las Minas (Cañete et al 2004). Evidencias similares se han detectado en otras zonas estuarinas del sur de Chile (Bravo 1984;Richter 1985;Bertrán et al 2001) También es necesario analizar cómo la presencia de diferentes tipos de sedimentos pueden generar estructuras poblacionales distintas o variaciones en la estructura de las comunidades macrobentónicas intermareales (Jaramillo et al 1984(Jaramillo et al , 1985(Jaramillo et al , 1993(Jaramillo et al , 2001.…”
Section: Discussionunclassified
“…Nuevas investigaciones deberán corroborar si el actual patrón de distribución espacial de S. uncina-tus o de la macrofauna intermareal de bahía Lomas puede obedecer a una disminución de la salinidad provocada por el río Side (Sanders et al 1965;Dávila et al 2002), o a cambios en la composición de los sedimentos, o cómo este aporte de agua dulce y la disminución de la salinidad puede fragmentar la población de este poliqueto, de un modo similar a como ha sido sugerido en Punta Arenas para una población del poliqueto Prionospio orensanzi afecta a descargas del río Las Minas (Cañete et al 2004). Evidencias similares se han detectado en otras zonas estuarinas del sur de Chile (Bravo 1984;Richter 1985;Bertrán et al 2001) También es necesario analizar cómo la presencia de diferentes tipos de sedimentos pueden generar estructuras poblacionales distintas o variaciones en la estructura de las comunidades macrobentónicas intermareales (Jaramillo et al 1984(Jaramillo et al , 1985(Jaramillo et al , 1993(Jaramillo et al , 2001.…”
Section: Discussionunclassified
“…However, "suspension feeders" presented their highest number of individuals in the outermost part of the lagoon where hydrodynamics ranged from moderate to high. It has previously been shown that the dominance of this trophic group is determined by hydrodynamics (Sanz 1986, Pearson and Rosenberg 1987, Bódis et al 2011) and the sediment grain size (Sanders 1958, Young and Rhoads 1971, Jaramillo 1984, Probert 1984. Concerning "carnivores", they reached their maximal proportion at the outer part of Papapouli Lagoon (ST3) as well as in station ST1, especially in winter and spring where the sea-inlet was open.…”
Section: Discussionmentioning
confidence: 99%
“…En contraste, a la tierra adyacente a los lagos de Chiloé (Cucao y Huillinco) se le da otro uso y, en general, los procesos de erosión apenas comienzan. Se encontró una diferencia significativa entre los lagos en cuanto al contenido de materia orgánica, pero el porcentaje de contribución es mayor que el citado para el cercano estuario de Queule por Jaramillo et al (1984) y la parte baja del Río Bío-Bío por Bertrán et al (2001).…”
Section: Stationunclassified